Pengaruh Tingkat Kesehatan Bank Perekonomian Rakyat (BPR) Di Jember Ditinjau Dari Aspek Keuangan Terhadap Manajemen Laba Tahun 2019-2023 - Evi Wahyuni; Dedy Wijaya Kusuma; Nurshadrina Kartika Sari (JAKUMA : Jurnal Akuntansi dan Manajemen Keuangan, 2024)
This research aims to determine and prove the influence of the health level of People's Economic Banks (BPR) in Jember in terms of financial aspects on Profit Management for 2019-2023. Where risk profile measured using ratios Non Performing Loan (NPL), Earnings measured using Return On Asset (ROA) and Net Interest Margin (NIM) as well as Capital measured using ratios Capital Adequacy Ratio (CAR). The population in this research is People's Economic Banks (BPR) registered with the Financial Services Authority (OJK) in 2019-2023. This research uses a sampling technique, namely Saturated sample / saturated sample so that a sample of 16 BPR is obtained. The data analysis method uses multiple linear regression analysis using IBM SPSS Statistics 25. The results of the research show that partially the ROA, NIM and CAR variables have no effect on earnings management. Meanwhile, the NPL variable influences earnings management. Simultaneously NPL, ROA, NIM and CAR influence earnings management